Gene Expression and Immunochemistry Analysis of ADAMTS-1 and Versican in Ameloblastoma - Osvaldo Rodrigues de Souza Neto; Hellen Thais Fuzii; Suély Vieira Da Silva; Vanessa Morais Freitas; João de Jesus Viana Pinheiro (International Journal of Dentistry)
Background. Ameloblastoma is a benign but locally invasive odontogenic epithelial tumor, associated with a high recurrence rate after treatment. The action of enzymes of the metalloproteinase family is important to the degraded extracellular matrix, contributing to invasion. Thus, this study aimed to investigate the gene and protein expression of ADAMTS-1 and versican in ameloblastoma. Materials and Methods. Twenty cases of ameloblastoma (n = 20) and ten dental follicles (DF) (n = 10) were used as a source for immunochemistry and quantitative RT-PCR for determining the protein and mRNA expressions of the concerned genes, respectively. Moreover, western blot and indirect immunofluorescence analysis were performed in AME cells. Results. ADAMTS-1 and versican were overexpressed in DF than ameloblastoma by RT-PCR. However, in the immunolocalization analysis, ADAMTS-1 was expressed in ameloblastoma more than in DF and versican immunostaining obtained a similar pattern between ameloblastoma and DF. Indirect immunofluorescence detected the ADAMTS-1 and versican expression in cell lines derived from ameloblastoma. Western blot from cell lysate and conditioned medium detected ADAMTS-1 bands representing full-length and different processed forms. Monensin treatment confined ADAMTS-1 in the cell cytoplasm. Versican fragments also were detected in different compartments, intracellular and conditioned medium, allowing the versican process by ADAMTS-1. Conclusion. This study showed a distinct expression of ADAMTS-1 and versican in ameloblastoma and DF, with ADAMTS-1 protein higher expression observed in ameloblastoma and possibly cleaved versican. These findings suggested that ADAMTS-1 may participate in tumor invasion, especially for the degradation of substrates (versican) in the ECM.